1997
DOI: 10.1021/bi962610a
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Divalent Magnesium by Escherichia coli Phosphoribosyl Diphosphate Synthetase

Abstract: The mechanism of binding of the substrates Mg x ATP and ribose 5-phosphate as well as Mg2+ to the enzyme 5-phospho-D-ribosyl (alpha-1-diphosphate synthetase from Escherichia coli has been analyzed. By use of the competive inhibitors of ATP and ribose 5-phosphate binding, alpha,beta-methylene ATP and (+)-1-alpha,2-alpha,3-alpha-trihydroxy-4-beta-cyclopentanemethanol 5-phosphate, respectively, the binding of Mg2+ and the substrates were determined to occur via a steady state ordered mechanism in which Mg2+ binds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…The kinetic mechanism of spinach PRPP synthase isozyme 3 was steady-state ordered Bi Bi with MgATP binding first and PRPP leaving last similar to that shown previously for S. typhimurium and E. coli PRPP synthases (21,28). In addition, spinach PRPP synthase isozyme 3 required free Mg 2ϩ as an activator, similar to what has been shown for the bacterial and human PRPP synthases (8,21,26,29).…”
Section: Discussionsupporting
confidence: 79%
“…The kinetic mechanism of spinach PRPP synthase isozyme 3 was steady-state ordered Bi Bi with MgATP binding first and PRPP leaving last similar to that shown previously for S. typhimurium and E. coli PRPP synthases (21,28). In addition, spinach PRPP synthase isozyme 3 required free Mg 2ϩ as an activator, similar to what has been shown for the bacterial and human PRPP synthases (8,21,26,29).…”
Section: Discussionsupporting
confidence: 79%
“…Steady-state kinetic analysis of the inhibition of S. enterica or E. coli PRPP synthase by substrate analogs revealed an ordered Bi-Bi mechanism with binding of Mg 2ϩ first, followed by MgATP and then ribose 5-phosphate (41,56,57). The ordered kinetic mechanism was further confirmed by equilibrium dialysis.…”
Section: Class I Prpp Synthasesmentioning
confidence: 77%
“…The active site must accommodate the substrates ribose 5-phosphate and MgATP. In addition, an overwhelming volume of research data has shown that an additional so-called free Mg 2ϩ is required for activity, because maximal activity is only obtained when Mg 2ϩ is added to the reaction mixture in excess of the MgATP concentration for both bacterial (35,45,(55)(56)(57)(58) and mammalian (59,60) PRPP synthases. Furthermore, most PRPP synthases may accept other divalent metal ions in place of Mg 2ϩ , and thus Mg 2ϩ may be regarded as a pseudosubstrate (45,56,58,61).…”
Section: Class I Prpp Synthasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mg 2ϩ ions are required to form the actual substrate MgATP and as an activator of the enzyme (8 -13). PRPP synthases from Salmonella typhimurium (8,14,15), Escherichia coli (11,16), Bacillus subtilis (10), human (17), and rat (18) possess an absolute requirement for P i as an activator and are subject to inhibition by ADP and for B. subtilis and mammalian enzymes also by GDP, which binds to a specific allosteric site. In addition, ADP competes with MgATP for binding to the active site.…”
mentioning
confidence: 99%